PENGGUNAAN MISA (MEDIA INTERAKTIF SIKLUS AIR) DALAM PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA PADA SISWA KELAS V SD NEGERI 1 NGADIKUSUMAN - Melati Ayu Febriana; Firdaus; Salis Irvan Fuadi (STKIP Subang, 2026)
This research was motivated by the low learning motivation and science learning outcomes of elementary school students, especially on the water cycle material which is abstract in nature and is still often taught using conventional methods. This study aimed to determine the effect of using MISA (Media Interaktif Siklus Air) in deep learning on students’ learning motivation and science learning outcomes in fifth grade students of SD Negeri 1 Ngadikusuman. This research used a quantitative approach with a quasi-experimental research design. The research sample consisted of fifth grade students divided into an experimental group and a control group. Data collection techniques were carried out through tests, questionnaires, observation, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing (t-test). The results showed that the use of MISA had a positive and significant effect on students’ learning motivation, indicated by a significance value of 0.000 < 0.05 and a t-value of 4.446 > t-table 2.032. In addition, the use of MISA also had a positive and significant effect on students’ science learning outcomes with a significance value of 0.000 < 0.05 and a t-value of 4.435 > t-table 2.032. These findings indicate that the use of interactive learning media can create more engaging learning experiences, increase student participation, and help students understand science concepts more concretely. Therefore, MISA is effective as a learning innovation to improve students’ motivation and science learning outcomes in elementary schools.